Multidimensional analysis of serving speed in volleyball players by position, sets, and league types: interactions and statistical differences - Altundag, E.; Soylu, C.; Akyildiz, Z. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Purpose Our study explores the multifaceted factors influencing serve speed in volleyball, including player position, match progression, and league level, providing actionable insights for performance optimization and injury prevention strategies.